Neonatal Sucrose and Internalizing Behaviors at 18 Months in Children Born Very Preterm - McLean, MA; Ranger, M; Bone, JN; Selvanathan, T; Au-Young, SH; Chau, CMY; Chau, V; Ly, L; Kelly, E; Synnes, A; Miller, SP; Grunau, RE (American Medical Association (AMA), 2025)
Importance: In the neonatal intensive care unit (NICU), neonates born very preterm (<33 weeks' gestation) are exposed to great numbers of painful procedures, which is associated with more internalizing (anxiety and depressive) behaviors later in childhood. Oral sucrose is commonly used in NICUs to treat acute procedural pain and is effective in reducing behavioral responses, but the long-term associations between oral sucrose and child behaviors have not yet been examined. Objective: To examine associations between cumulative neonatal pain and sucrose exposure in early life (prior to approximately 32 weeks postmenstrual age), in relation to child behaviors (internalizing and externalizing) at 18 months corrected age (CA) in children born very preterm and to examine whether the associations are sex specific. Design, Setting, and Participants: In a prospective, longitudinal cohort study, children born very preterm (24-32 weeks' gestational age [GA]) were recruited from 2015 to 2019 from 3 tertiary NICUs in Canada and attended a follow-up visit at 18 months CA. Data analysis was performed from February to May 2024. Exposures: The clinical protocol to treat acute procedural pain at site 1 was facilitated tucking with nonnutritive sucking; sites 2 and 3 used 24% sucrose with nonnutritive sucking. Prospective clinical record review was conducted (eg, number of painful procedures, cumulative sucrose dose, analgesia, sedation, days receiving mechanical ventilation, and surgical procedures). Main Outcomes and Measures: Parents reported on their child's behavior on the Child Behavior Checklist (CBCL; 1.5 to 5 years) yielding internalizing and externalizing scores. Results: In total, 192 children (110 male [57%]) were included in the current study. After applying propensity score weights to adjust for clinical factors across sucrose and nonsucrose sites and accounting for neonatal pain, cumulative sucrose (milliliters) in early life was not associated with internalizing scores (B = 0.62; 95% CI, -0.46 to 1.99). However, greater neonatal pain exposure was significantly associated with higher 18-month CBCL internalizing scores (B = 0.01; 95% CI, 0.0003 to 0.0135; R2 = 1.8%). There were no associations with externalizing scores, and associations were not moderated by child sex. Conclusions and Relevance: In this cohort study of children born very preterm across 3 tertiary NICUs in Canada, cumulative sucrose exposure in early life demonstrated no association with child behavior and did not ameliorate the association between greater neonatal pain and internalizing behaviors. Further research is needed to identify pain management strategies that can effectively mitigate or protect against adverse behavioral outcomes in children born very preterm.
Keywords: 3213 Paediatrics; 32 Biomedical and Clinical Sciences; Chronic Pain; Prevention; Pediatric; Pain Research; Clinical Research; Perinatal Period - Conditions Originating in Perinatal Period; Preterm, Low Birth Weight and Health of the Newborn; Behavioral and Social Science; Neurosciences; Basic Behavioral and Social Science; Reproductive health and childbirth; 32 Biomedical and clinical sciences; 42 Health sciences; Sucrose; Female; Male; Infant; Prospective Studies; Infant, Newborn; Infant, Extremely Premature; Longitudinal Studies; Intensive Care Units, Neonatal; Pain, Procedural; Canada; Child Behavior; Anxiety